Studi Pertumbuhan Awal Kuya Batok (Cuoro Ambonensis) di Kolam Kehutanan UNIB serta Implementasinya sebagai Bahan Ajar Zoologi Vertebrata - Indah Maryani; Aceng Ruyani; Bhakti Karyadi; Hery Suhartoyo (PendIPA Journal of Science Education, 2018)
ABSTRACT[Study of Kuya Batok (Cuoro Ambonensis) Early Growth’s in UNIB Forestry Pond and its Implementation as Teaching Materials on Vertebrate Zoology]. The goal of this study was to know the growth of C. amboinensis in the ex-situ conservation area of the University of Bengkulu Forestry Pond during the 10 weeks study and 3 weeks continuous research, to know the condition of abiotic factor C. amboinensis in ex-situ conservation area of Forest Ponds of Bengkulu University, and to know the knowledge and understanding of the students about the early growth of C. amboinensis, the conservation concept at the University of Bengkulu Forestry Pond and the change of students conservation attitude by using teaching materials. Implementation of learning adoption of existing teaching material products "Technique Monitoring of Black-turtle Lineage of Coldhamii" (Astuti, 2016). The teaching material is in the form of a book entitled "Monitoring Technique of Turtle Shell (Cauro amboinensis)". The results of this study show that: a) The first study only received 1 C. amboinensis for 10 weeks of observation and growth (weight, length, width, thickness, anterior-posterior arch, b) Abiotic factors in the conservation area supported growth of C. amboinensis and suitable for in situ conservation pond ex situ in UNIB, c) On the second observation release 15 C. amboinensis by using 3 large trapp to conservation pond for 3 weeks and experiencing growth, d) condition of abioic factor become habitat C. amboinensis include: ground temperature 280C, water temperature 300C, relative humidity 80%, soil pH 6, pH 7 water, turbidity 80, e) high knowledge of students about the existence of turtles 22.8% - to 77.2% on conservation 13% to 87%, not in line with the conservation attitude of 34% to 66%.Keywords: Growth; C. amboinensis; abiotic factor; teaching material.